Peran Motivasi Kerja Dalam Memoderasi Hubungan Antara Kepemimpinan Terhadap Semangat Kerja Karyawan - Permadi, I Komang Oka; Rasminingsih, Ni Kadek Nonik (Politeknik Negeri Ambon, 2023)
Introducing leadership into any organization involves the careful structuring of its mechanisms and functions. It is widely acknowledged that when a leader possesses a strategic position and a set of crucial skills, they have the potential to enhance or even transform the company. The objective of this research is to confirm and reevaluate the role of work motivation in moderating the relationship between leadership and employee morale. This study employs nonprobability sampling with a saturation sampling technique to determine the sample size, encompassing a total of 42 individuals from the entire population. Path analysis is utilized to test the hypotheses using the Partial Least Square (PLS) method through SmartPLS software version 3.2.9. The research findings conclusively establish that leadership has a significant impact on employee morale, while the role of motivation does not appear to strengthen or weaken the relationship between leadership and employee morale.